Auditing - Millichamp, A.H. (Alan H). 4 0 16; Taylor, John; 5 (Andover, Hampshire, UK : Cengage Learning, 2012)
This comprehensive textbook provides up-to-date coverage of auditing in an accessible style and clearly explains the key features of auditing in short, easily readable sections that promote effective learning.
Includes bibliographical references and index.
Keywords: 2 -- 0; 6; Auditing. -- 20; 20; 2